Aksiologi Pendidikan Islam - ILHAM AKBAR; MAHMUD ARIF; JANUARIANSYAH ARFAIZAR (Raudhah - Proud To Be Professional, 2021)
Islamic teachings are a set of value systems which are Islamic life guidelines in accordance with the commands and guidance of Allah SWT. With this, Islamic education is certainly an activity that directs a person's development intentionally and in line with Islamic values. It is certainly interesting for the author to examine the Axiology of Islamic Education. The research method in this discussion is library research. The results of the study show that the axiology of Islamic education is related to the goals, targets, and values ​​to be achieved in Islamic education. Values ​​based on their nature are divided into immanent and subjective, universal and objective, absolute and relative. The values ​​of Islamic education are the characteristics or things inherent in Islamic education that are used as a human basis to achieve the goal of human life, namely to serve Allah SWT. The values ​​of Islamic education contained include the value of worship, the value of ihsan, the value of the future, the value of mercy, the value of trust and the value of da'wah.